Laser ablation for material processing. Issue 1 (1st February 2022) - Cutroneo, M.; Havranek, V.; Mackova, A.; Malinsky, P.; Silipigni, L.; Slepicka, P.; Fajstavr, D.; Torrisi, L.
Abstract : The laser ablation is an established material processing for many applications in nanotechnology, materials science and biomedicine. The laser ablation can be carried out in vacuum, in air and in liquid. Laser ablation mechanisms and their products depend on laser fluence, wavelength, pulse duration, ablation environment as well as target composition, density, thickness, roughness. This contribution is addressed to laser ablation of solid targets with the aim of hot plasma generation and thin film deposition on substrates located in appropriate positions in vacuum and in air. In the first section is presented an example of forward and backward plasma accelerations using the sub-nanosecond laser at the PALS laboratory (Czech Republic) for pulsed laser deposition processing. In the second section is reported the use of a nanosecond laser coupled to a post-accelerating compact system employed at the INFN in Catania (Italy) to ablate germanium solid targets in vacuum and to deposit thin films on SiO2 /Si substrates to modify their native features. The last section is focused on the use of the nanosecond laser at the Tandetron laboratory (Czech Republic) employed for pulsed laser deposition and laser-induced backward transfer processing in vacuum and in air.